Revealing the Relationship Between Financial Management and Student Investment Decisions at Bandung State Polytechnic - Nurfadhilah, Muhamad Imam; Za’im, Zahir Muhammad (International Journal Administration, Business & Organization, 2025)
This study investigates the relationship between financial management and investment decisions among students. Data were collected from one hundred active students who were randomly selected using a descriptive quantitative approach and a standard questionnaire. The factors studied include students' preferences for investment instruments, such as savings, deposits, mutual funds, and other financial assets, as well as financial management techniques, such as planning, control, and personal financial recording. The purpose of this research is to determine how financial management techniques influence students' decisions regarding various investment instruments. The results show that there is a strong correlation between students' investment decisions and their capacity in financial management. Although students with less developed financial management understanding prefer more conventional or common choices such as savings, students with proficient financial management skills usually have habits of diversifying investments or selecting several investment instruments and choosing instruments with low risk. The findings of this study provide an overview of the importance of financial behavior among students and serve as a basis for the development of more effective financial literacy programs.